Clinical, Radiological and Histological Features and Their Association with Extranodal Extension in Buccoalveolar Complex Squamous Cell Carcinoma - Anto, Ronald; Riju, Jeyashanth; Chinniah, Praveen; Tirkey, Amit Jiwan; Chamania, Gaurav; Patil, Shruthi; Bhandari, Subhan; Paulose, Antony; Vidya, Konduru; Karuppusami, Rekha; Babu, Ramesh; Micheal, Rajiv C. (South Asian Journal of Cancer, 2023)
Objectives The study was aimed to (1) evaluate the effectiveness of clinical examination, intraoperative finding, and contrast-enhanced computed tomography (CECT) to detect extranodal extension (ENE) in buccoalveolar complex squamous cell carcinoma (BAOSCC), (2) to know various factors influencing ENE, and (3) to evaluate survival outcome in patients with ENE.Materials and Methods This was a retrospective cohort study, which included 137 patients with BAOSCC who underwent curative treatment between May 2019 and April 2021. Collaborative findings suggestive of ENE were noted during preoperative clinical examination, CECT, and intraoperatively, and their efficacy was compared with postoperative histopathology. Also, the various factors associated with ENE were evaluated and compared.Statistical Analysis Univariate and multivariate analysis of parameters was done using multiple logistic regression analysis and significant correlation was determined using chi-square test between ENE positive and negative categories. Analysis of prognosis and survival was done by Kaplan–Meier curve plotting using regression analysis and its significance was compared.Results The overall prevalence of ENE was 18.98% and that of lymph node involvement was 40.88%. CECT (73.1%) was found to be more sensitive in detecting ENE compared to intraoperative examination (46.2%) and clinical examination (34.6%).In comparison with clinical examination (91.9%) or CECT (78.38%), intraoperative examination (93.7%) showed the highest specificity in detecting ENE. Clinical nodal size ≥ 3 cm (p ≤ 0.001), fixity (p ≤ 0.001), and clinical number of nodes (p ≤ 0.001) had significant association with ENE. The presence of thick nodal walls on CECT increased the probability of predicting ENE 15 times (p = 0.180, confidence interval: 0.3–765.4). After a mean follow-up of 18 months, subjects without nodal positivity had a survival advantage over patients with positive lymph nodes (86.4% vs. 53.3%) and those with ENE (86.4% vs. 23.2%), respectively.Conclusion The results demonstrated that clinical examination can be used as an adjuvant to radiological imaging for prediction of ENE preoperatively. Clinical finding suggesting size of node ≥ 3 cm and ≥ 2 nodes are strong predictor of ENE, in addition to other known predictors. Patients with ENE had an unfavorable prognosis when compared with subjects with metastatic nodes without ENE. Presence of ENE remains one of the strongest factors predicting recurrence and thus poor prognosis.
Keywords: oral squamous cell carcinoma; extranodal extension; contrast-enhanced computed tomography; prognosis; oral cancer; neck metastasis